Hedge funds strategies: Are they consistent? - Mendes-Ribeiro, Mafalda (2017)
Alternative investment has grown considerably, transforming this industry in the forefront of investment innovation. Despite their public acknowledgment and profound influence in the financial market, there is still relative small understanding about hedge funds strategies style. This paper intends to determine whether stylistic characterization exists across hedge fund strategies, by comparing, for the period of 1998 to 2008, the performance of the EDHEC indices with one of the most representative indices of hedge funds, the CSFB/Tremont index, regarding seven main strategies. The results do not reject the hypothesis of equal mean monthly returns on every strategy, comparing the two data sources, showing that there is no significant differences between the strategies analyzed, suggesting that the purity in each style is not as developed and accurate as we may suppose.